2015
DOI: 10.1111/resp.12728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muc5b promoter polymorphism on disease predisposition and survival in idiopathic interstitial pneumonias

Abstract: Background and objective: A common polymorphism in the MUC5B gene (rs35705950) is associated with susceptibility to idiopathic pulmonary fibrosis (IPF) and familial interstitial pneumonia (FIP). We investigated predisposition of the MUC5B polymorphism to fibrotic interstitial pneumonias in Dutch Caucasian patient cohorts. Furthermore, we investigated the correlation between MUC5B genotype and survival in these cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 22 publications
(67 reference statements)
5
45
0
1
Order By: Relevance
“…IPF is a rare non-infectious pulmonary aging disease of unknown cause characterized by insidious onset of disease in patients without a history of pulmonary infection. Subsequent research showed that the MUC5B T-allele not only predisposes to IPF but to a variety of chronic progressive forms of pulmonary fibrosis [24][25][26][27] . The key cell in the pathogenesis of pulmonary fibrosis is the alveolar type II (AT2) cell.…”
Section: Discussionmentioning
confidence: 99%
“…IPF is a rare non-infectious pulmonary aging disease of unknown cause characterized by insidious onset of disease in patients without a history of pulmonary infection. Subsequent research showed that the MUC5B T-allele not only predisposes to IPF but to a variety of chronic progressive forms of pulmonary fibrosis [24][25][26][27] . The key cell in the pathogenesis of pulmonary fibrosis is the alveolar type II (AT2) cell.…”
Section: Discussionmentioning
confidence: 99%
“…This association is maintained in all tested populations that had greater than a 1% prevalence of the minor allele including Mexican [84], Chinese [85] and Japanese cohorts [86] but not in a Korean population where the allele frequency was less than 1% [84]. The MUC5B promoter variant is also associated with phenotypic variability in IPF including prevalence of ground glass opacities, subpleural axial distribution of fibrosis, and survival [82,[165][166][167][168][169][170][171]. The MUC5B promoter polymorphism is also associated with increased prevalence of interstitial abnormalities in asymptomatic controls [172] suggesting the utility of rs35705950 in the early detection of IPF.…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation by Fingerlin et al [40 && ] identified an additional novel locus within human leukocyte antigen (HLA) complex, underscoring the potential role that impaired host defense plays in IPF pathogenesis. In addition to their association with IPF susceptibility, SNPs within MUC5B and TOLLIP have also been linked to differential survival, though the strength of association varies depending on the cohort under consideration [36,[41][42][43]. A recent pharmacogenetic investigation [44 && ] also showed that a common SNP within TOLLIP may also modulate the response to N-acetylcysteine therapy, an antioxidant commonly used to treat IPF before a phase III clinical trial failed to demonstrate efficacy [45].…”
Section: Genetic Subgroupsmentioning
confidence: 99%